Normalization of physical tests` results can attenuate the relative age effect in young Swiss alpine skiers - Gorski, T.; Hoppeler, H.; Rosser, T.; Beltrami, F. G.; Vogt, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The occurrence of the relative age effect (RAE), characterized by an over-representation and/or better performance of athletes born in earlier year quarters (Q) of the competitive calendar in comparison to those born in later Qs, has been reported in several sports. Recently, we demonstrated the occurrence of the RAE in young Swiss alpine skiers. This study analyses the effect of normalizing results in physical tests to weight and height on the occurrence of RAE in Swiss alpine skiers between 11 and 19 years old. Methods: The Swiss Ski Power Test includes anthropometric data assessment, endurance (Cooper test, high-box jump), strength (one-leg and two-legs 5-hop, standing long jump, push-ups), and speed and coordination (two circuits containing obstacles) tests. Data of 6996 tests carried out with 1031 female and 1438 male athletes between 2004 and 2010 were analyzed, with athletes being divided according to sex and category (K1: 11-12 years old, K2: 13-14 years old, JUN1: 15-16 years old, JUN2: 17-19 years old). One-way ANOVAs were used to assess differences between athletes born in different Q for non-normalized results and results normalized to height and weight for each test of each category and sex. Significance level was set at p < 0.05. Results: Significant differences in performance between athletes born in different Q (i.e., RAE) were found in several tests for different categories, with RAE occurring in a higher number of tests in categories K1 (male) and K2 (female) in comparison with other categories. For female and male athletes, normalization to height, but not to weight, reverted RAE in most cases. In female athletes, normalization to height, but not weight, was able to revert RAE in all tests of all categories in which RAE was present but the Cooper test of JUN2 athletes. Nevertheless, in male JUN2 skiers normalization to weight seemed to be more adequate than normalization to height. Reverting the RAE using normalization was not possible in some tests (mainly strength tests) of male K2 and JUN1 athletes. Discussion: Normalization of performance in physical tests to height - and, in some cases, to weight - seems to be a possibility of attenuating RAE occurrence in young alpine skiers. Generally, normalization to height reverted more RAE cases than normalization to weight. RAE cases not reverted by normalization highlight the role played by other factors than anthropometric variables in the development of RAE. Based on these results, normalization to height is recommended when such tests are used for comparisons between athletes born in different Q or talent selection, for example.